Praktek Cerai Rujuk di Desa Pedamaran Menurut Hukum Islam dan Hukum Positif - Lestari Lestari; Siti Zailia; Legawan Isa (Muqaranah, 2022)
Referral divorce practices must be carried out in the Religious Courts. However, there are still many people who divorce and reconcile without involving the Religious Courts, as is often done by people in Pedamaran Village, Pedamaran District, Ogan Komering Ilir Regency, South Sumatra. Therefore, this research wants to know about the implementation of the divorce practice in Pedamaran Village which will be studied in terms of Islamic law and applicable legislation. The aim of the research is to find out how the study of Islamic law and legislation regarding the practice of divorce is referred to in Pedamaran Village. This type of research is field research, meaning that this research is carried out directly on the research object to obtain complete data. The data collection techniques in this study were carried out using observation, interview and documentation techniques. The approach method uses the comparative method. The results of the study show that the practice of referral divorce carried out by the Pedamaran village community is in accordance with Islamic law, so that the practice of referral divorce is legal. However, according to Law Number 16 of 2019, the practice of divorce and reconciliation in Pedamaran Village is illegal, because the divorce was not carried out at the Religious Court and reconciliation was not carried out in front of the marriage registrar. This shows that there are still many people who have not complied with the applicable laws and regulations, so it is necessary to hold socialization so that people are aware of the law.